S100A4 hypomethylation affects epithelial–mesenchymal transition partially induced by LMP2A in nasopharyngeal carcinoma. Issue 10 (21st August 2015) - Lin, Zhe; Deng, Lei; Ji, Jie; Cheng, Ci; Wan, Xin; Jiang, Runqiu; Tang, Junwei; Zhuo, Han; Sun, Beicheng; Chen, Yun
Abstract : To identify cellular target genes involved in NPC cell invasion and metastasis, gene expression profiles of CNE‐1 cells with or without ectopic LMP2A expression were compared by using the metastatic gene array. S100 calcium binding protein A4 (S100A4) was the highest increased one among these genes both in mRNA and protein levels of NPC cells. Moreover, S100A4 was upregulated in LMP2A‐positive NPC tissues. We found that CNE‐1‐S100A4 showed significantly increased invasion ability as compared to the controls both in vitro and in vivo, which indicated that S100A4 induced EMT occurrence and promoted metastasis. Notably, the DNA hypomethylation of S100A4 was found in LMP2A‐positive NPC tissues. Besides, inhibition of DNA methyltransferases via 5‐Aza‐dC stimulated the expression of S100A4 in the cells without ectopic LMP2A expression. The methylation changes were confirmed by methylation specific PCR (MSP), suggesting that LMP2A ectopic expression led to the demethylation of S100A4 promoter. These results demonstrated that LMP2A‐induced hypomethylation participated in regulating S100A4 expression in NPC. Our findings provide an evidence for the emerging notion that hypomethylation and activation of correlated genes are crucial for metastasis progression in cancer. © 2015 Wiley Periodicals, Inc.